Effect of eye NGF administration on two animal models of retinal ganglion cells degeneration - Valeria Colafrancesco; Marco Coassin; Simona Rossi; Luigi Aloe (Istituto Superiore di Sanità, 2011)
The aim of this study was to investigate the effect of nerve growth factor (NGF) administration on retinal ganglion cells (RGCs) in experimentally induced glaucoma (GL) and diabetic retinopathy (DR). GL was induced in adult rats by injection of hypertonic saline into the episcleral vein of the eye and diabetes (DT) was induced by administration of streptozoticin. Control and experimental rats were treated daily with either ocular application of NGF or vehicle solution. We found that both animal models present a progressive degeneration of RGCs and changing NGF and VEGF levels in the retina and optic nerve. We then proved that NGF eye drop administration exerts a protective effect on these models of retinal degeneration. In brief, our findings indicate that NGF can play a protective role against RGC degeneration occurring in GL and DR and suggest that ocular NGF administration might be an effective pharmacological approach.